2000
DOI: 10.1007/s11920-996-0019-x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid medical illness in psychiatric patients

Abstract: Patients with psychiatric illnesses may be at higher risk for the development of certain medical problems. Those with more severe psychiatric illnesses may encounter barriers to promoting good health and to obtaining good health care when comorbid illnesses do occur. This paper reviews some of the recent literature on health care practices and health system access for the mentally ill; HIV care and its relationship to mental disorders; drug interactions between general medical drugs and psychotropics; and cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 58 publications
1
27
0
2
Order By: Relevance
“…There may, however, be barriers to people with mental illness accessing good quality care [18]. In the United States, Druss et al [19] reported that older people with mental illnesses did not always receive high quality care after a myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…There may, however, be barriers to people with mental illness accessing good quality care [18]. In the United States, Druss et al [19] reported that older people with mental illnesses did not always receive high quality care after a myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Also, people with co-morbid medical disorders have poorer medical outcomes which raise concerns about their access to care and quality of treatment (Chwastiak et al 2006;Essock et al 2003;Fremont et al 2007;Goldman 2000;Massad et al 1990;Salsberry et al 2005). In a study by Druss et al (2002), persons with psychiatric disorders received fewer preventive medical services and individuals with co-morbid mental disorders were less likely to receive coronary revascularization procedures than those without mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Bezüglich der Inanspruchnahme von Vorsorgeuntersuchungen liegen keine systematischen Untersuchungen vor, bez. der Inanspruchnahme somatisch-medizinischer Behandlung sind die Ergebnisse widersprüchlich und stammen vorwiegend aus anderen Gesundheitssystemen [3,5,6]. Vor dem bekannten Hintergrund häufig mangelnder Medikamentenadhärenz und fehlender Krankheitseinsicht könnte auch im somatisch-medizinischen Bereich eine mangelnde Selbstfürsorge vermutet werden.…”
unclassified